District nurses and general practitioners' negotiation of responsibility for nutritional care for patients in palliative phases cared for at home. (10th December 2020) - Berggren, Erika; Törnkvist, Lena; Ödlund Olin, Ann; Orrevall, Ylva; Strang, Peter; Hylander, Ingrid
Abstract: Aim: To explore district nurses and general practitioners (GPs) interaction in a case seminar when discussing nutritional care for patients in palliative phases cared for at home and to construct a theoretical model illuminating the professionals' main concern. Background: Nutritional care for people who are frail and older requires collaboration between nurses and physicians in primary health care. However, both collaboration and knowledge need to be improved, and there is a lack of continuing interprofessional education to meet these needs. We therefore developed an interprofessional educational intervention about nutritional care for patients in palliative phases of disease that was adapted to primary home health care and ended with a case seminar. The case seminar discussions gave us the opportunity to study micro-level interactions between district nurses and GPs in a learning context. Methods: Grounded theory method was used to construct a theoretical model of the interactions between district nurses and GPs as they discussed an authentic case. Findings: A substantive grounded theory that illuminates how district nurses and GPs interacted, negotiating responsibility for nutritional care for patients in palliative phases cared for at home. The theory is described in a tentative theoretical model that delineates factors that facilitate interprofessional dialogue and lead to interprofessional learning, or block such dialogue and learning. The theoretical model illuminates the importance of a distinction between uniprofessional and interprofessional dialogue in interprofessional educational interventions. It suggests that interprofessional learning was generated directly from the interaction between district nurses and GPs in the case seminar discussions. The model can be used to promote better teamwork and collaboration in caring; for example, as a basis for reflection in collaborative and interprofessional learning interventions and as a tool for facilitators and teachers.